2015
DOI: 10.1155/2015/415024
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation as a Keystone of Bone Marrow Stroma Alterations in Primary Myelofibrosis

Abstract: Primary myelofibrosis (PMF) is a clonal myeloproliferative neoplasm where severity as well as treatment complexity is mainly attributed to a long lasting disease and presence of bone marrow stroma alterations as evidenced by myelofibrosis, neoangiogenesis, and osteosclerosis. While recent understanding of mutations role in hematopoietic cells provides an explanation for pathological myeloproliferation, functional involvement of stromal cells in the disease pathogenesis remains poorly understood. The current do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
71
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 150 publications
1
71
0
Order By: Relevance
“…PDGF has long been implicated in the development of BM fibrosis in MPN along with TGF-β and bFGF (57,69,70). Mainly produced by megakaryocytes, PDGF is primarily stored and released from α granules in megakaryocytes and platelets, but production in fibroblasts, osteoblasts, and endothelial cells has also been delineated (57).…”
Section: Gemm) Colonies (mentioning
confidence: 99%
“…PDGF has long been implicated in the development of BM fibrosis in MPN along with TGF-β and bFGF (57,69,70). Mainly produced by megakaryocytes, PDGF is primarily stored and released from α granules in megakaryocytes and platelets, but production in fibroblasts, osteoblasts, and endothelial cells has also been delineated (57).…”
Section: Gemm) Colonies (mentioning
confidence: 99%
“…Its elevated levels are also characteristic for the primary myelofibrosis. 34,35 It has been proposed that CD34 C blasts are the major producers of IL8 in BM of MDS patients, 32 because the initially elevated levels of IL8 in BM serum of MDS or AML patients subsequently decrease with the complete remission and disappearance of CD34 C blasts. Later, Schinke et al detected the elevated IL8 transcripts in AML/MDS BM samples.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic inflammation sustained by the continuous release of proinflammatory cytokines and chemokines and subsequent bone marrow microenvironment alterations are considered key factors in PMF pathogenesis. The abnormal production of cytokines that occurs both in malignant and nonmalignant cells was related to an increased JAK2-STAT3 activation and was found responsible for the inhibition of apoptosis and increased myeloproliferation, creating an environment that favors MPN clone maintenance and expansion [31,32]. Recently, it was shown that MF cells downregulated the expression of X-linked inhibitor of apoptosis (XIAP) and mitogen-activated protein kinase 8 (MAPK 8), a necessary component of TNFmediated apoptosis, via a TNF/TNFR2-dependent autocrine loop.…”
Section: Intrinsic And/or Extrinsic Apoptotic Pathways Involved In Mpmentioning
confidence: 99%